Reposisi Guru Pendidikan Agama Islam di Sekolah Dasar Kota Manado - Rommy Cahya Nahu; Muh Idris; Ishak Talibo (Institut Agama Islam Negeri (IAIN) Manado, 2019)
Abstrak: Penelitian ini bertujuan untuk menganalisis tentang posisi guru pendidikan agama Islam di Sekolah Dasar Kota Manado. Metode yang digunakan dalam membedah atau menganalisis penelitian ini adalah metode kualitatif untuk memberikan pemetaan posisi guru pendidikan agam Islam di Sekolah Dasar Kota Manado sebagai gambaran tentang bentuk reposisi guru agama Islam serta usaha yang dilakukan oleh pemerintah Daerah Kota Manado. Penelitian ini berlokasi di Sekolah Dasar Negeri di Kota Manado. Berdasarkan hasil penelitian ini ditemukan bahwa: Reposisi guru agama Islam di Sekolah Dasar Negeri Kota Manado terjadi karena adanya inisiasi guru agama Islam lainnya untuk mengisi posisi guru agama Islam dalam pembelajaran pendidikan agama Islam karena posisi guru agama Islam di posisikan oleh guru yang bukan berlatar belakang guru pendidikan agama Islam dan bahkan bukan guru yang beragama Islam. Selain itu reposisi guru agama Islam di Sekolah Dasar Negeri Kota Manado terjadi disebabkan adanya guru agama Islam mengambil jadwal mengajar di Sekolah lain yang tidak memiliki guru agama Islam guna untuk memenuhi kekurangan jam.Abstract : This study aims to analyze about the position of Islamic education teachers in Elementary Schools in Manado city. The method used in dissecting or analyzing this research is a qualitative method. It is to provide a mapping of the position of Islamic education teachers in Manado City Elementary Schools as an illustration of the form of repositioning the Islamic education teachers and the efforts made by the local government of Manado City. This research is located at the State Elementary Schools in Manado City. Based on the results of this study, it is found that: The reposition of Islamic education teachers in Manado City Elementary Schools occurred due to the initiation of Islamic education teachers to reallocate Islamic education teachers in Islamic education learning because the position of Islamic education teachers was positioned by teachers who were not having educational teachers background and not even a Muslim teacher. In addition, the reposition of Islamic education teachers in Manado City Elementary Schools occurred due to the existence of Islamic education teachers in taking teaching schedules at other schools which do not have Islamic education teachers in order to meet the shortage of hours. Kata Kunci: Reposisi, Guru Pendidikan Agama Islam, Sekolah Dasar.